Thinking of deduction level students in proving theorem of triangle and its convers based on the steps of Polya - Erfan Yudianto; Niken Shofiana Dewi; Toto Bara Setiawan (STKIP PGRI Banjarmasin, 2021)
Proving ability is rarely homed in mathematics learning. Thus, this becomes interesting when examined and associate it with van Hiele’s level of geometrical thinking, namely the level of deduction. This study aims to determine the thinking process of student’s level deduction in proving Triangle Proportionally Theorems and its convers. This type of research is qualitative research. Deduction level students were given a theorem proving test consist of two questions, then conducted interviews to find out more about the thinking process. The results are students level deduction can prove the theorem by utilizing the knowledge possessed both undefined terms (point and line), parallel and similarity AAA postulates, definitions of angle and congruence, parallel and similarity SAS theorems, corollary CSSTP and CASTC. It can be known from the student’s proving scheme and interviews that is conducted by researcher towards student.